Perkembangan Five Power Defence Arranggements dalam Menanggapi Dinamika Keamanan Asia Tenggara pasca Perang Dingin - Pratama, Caroline Putri; Candra, Darang Sahdana (Global: Jurnal Politik Internasional, 2014)
The Five Power Defence Arrangements (FPDA) is a regional security institution in Southeast Asia, with Malaysia, Singapore, Australia, New Zealand, and United Kingdom as its members. As one of the oldest, and still existing, regional security institution in the Southeast Asia region, FPDA’s existence seems to be unheard of, compared to the region’s Association of Southeast Asian Nations (ASEAN) or even the Cold War’s Southeast Asia Treaty Organization (SEATO). Although FPDA was created in the height of the Cold War, as well as in response to the potential hegemonic Indonesian threat to former British colonies, the institution is still exist even after both original existential threat wanes. In the end, how the FPDA can maintain its existence in the changing security dynamics in the region, especially after the end of the Cold War, is an interesting piece of puzzle to be solved.